2017
DOI: 10.1002/anie.201703970
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Engineering of Lead‐Free Double Perovskite Cs2AgBiBr6 through Trivalent Metal Alloying

Abstract: The double perovskite family, A M M X , is a promising route to overcome the lead toxicity issue confronting the current photovoltaic (PV) standout, CH NH PbI . Given the generally large indirect band gap within most known double perovskites, band-gap engineering provides an important approach for targeting outstanding PV performance within this family. Using Cs AgBiBr as host, band-gap engineering through alloying of In /Sb has been demonstrated in the current work. Cs Ag(Bi M )Br (M=In, Sb) accommodates up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
419
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 466 publications
(449 citation statements)
references
References 35 publications
23
419
0
1
Order By: Relevance
“…The significant bandgap reduction is caused by the Tl impurity-induced band edge reconstruction, which is supported by DFT results (Figure 16f). [197] They found that Sb alloying decreases the bandgap slightly, with the smallest value of 1.86 eV for Cs 2 Ag(Bi 0.625 Sb 0.375 )Br 6 ( Figure 16g). However, Tl is highly toxic and, therefore, undesirable for photovoltaic applications.…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 97%
See 3 more Smart Citations
“…The significant bandgap reduction is caused by the Tl impurity-induced band edge reconstruction, which is supported by DFT results (Figure 16f). [197] They found that Sb alloying decreases the bandgap slightly, with the smallest value of 1.86 eV for Cs 2 Ag(Bi 0.625 Sb 0.375 )Br 6 ( Figure 16g). However, Tl is highly toxic and, therefore, undesirable for photovoltaic applications.…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 97%
“…[196] Moreover, they have shown that the Tl-alloyed Cs 2 AgBiBr 6 also exhibit long-lived carriers. [197] The bandgap reduction is attributed to the higher energy levels of Sb 5s states than that of Bi 6s states, which slightly raises the VBM. Du et al have demonstrated bandgap engineering of Cs 2 AgBiBr 6 through alloying of trivalent cations such as Sb 3+ .…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…[145] Staying within the given x range, the double perovskite phase is maintained. The complex nature and the impact of atomic substitution on the optoelectronic character within the double perovskite family are highlighted in substituted double perovskites, Cs 2 AgBi 1−x In x Br 6 (x = 0, 0.25, 0.5, and 0.75) and Cs 2 AgBi 1−x Sb x Br 6 (x = 0, 0.125, and 0.375).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%